Proceso de ASC - DISEÑO DE HERRAMIENTAS PEDAGOGICAS FACILITAR EL USO DEL CANVAS DE MODELOS DE NEGOCIOS FLORECIENTES EN PYMES DEL VALLE DE ABURRA (2022)
Internationally, theories and tools have begun to emerge that aim to bring companies closer to sustainability. One of these theories is the Ontology of Strongly Sustainable Business Models (Upward, 2014). From this theory, the Flourishing Enterprises Business Model Canvas (FBMC) was developed, a tool that encourages companies to consider, in addition to the traditional aspects of a business model, other necessary aspects for their business to contribute to the flourishing of life on the planet. This project aims for students in the SIIE research group to understand the FBMC tool for developing business models and the theory that supports it in order to design a didactic tool, such as an interactive book, that facilitates its communication and appropriation by young people and students aged 15 to 25 in the Aburrá Valley. The validation process of the interactive book will be documented to investigate the impact that the use of such tools can have on expanding the knowledge and understanding of young people regarding the FBMC theory and the construction of sustainable business models.